Negative electrode sheet, cylindrical battery, and electric device
Patent Information
- Application Number
- CN202611262598.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-30
AI Technical Summary
为提升负极容量,常采用硅基材料,如硅碳复合材料;然而,硅碳复合材料通常具有较高的比表面积,导致在首次充放电过程中电解液在其表面大量分解形成固体电解质界面膜,消耗大量活性锂,使得首次库仑效率(ICE)偏低;且硅/碳之间的结合力不足,在卷绕与循环膨胀压力下易发生脱嵌等
本发明中的负极极片,通过将复合微球的比表面积控制在1~5m2/g的极低范围,并满足C5/C0.2≥0.80,大幅减少了首次充放电过程中电解液在活性材料表面分解形成SEI膜所消耗的活性锂,使初始库仑效率提升至85%以上,无需额外预锂化处理;同时,极低的比表面积限制了循环过程中电解液与内部硅的持续接触,有效抑制了副反应,提高了长循环的容量保持率。此外,复合微球在5C大倍率放电条件下仍能保持较高的可逆容量,兼顾了高能量密度与快充能力。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a negative electrode sheet, a cylindrical battery, and an electrical device. Background Technology
[0002] In recent years, all-tab cylindrical lithium-ion batteries, due to their large size and all-tab current collector design, have significantly reduced internal resistance and improved fast charging capabilities, becoming an important technological route for high-energy-density power batteries. To improve the negative electrode capacity, silicon-based materials, such as silicon-carbon composites, are often used. However, silicon-carbon composites typically have a high specific surface area, leading to the electrolyte decomposing extensively on their surface during the first charge and discharge process to form a solid electrolyte interface film, consuming a large amount of active lithium and resulting in a low initial coulombic efficiency (ICE). Furthermore, the bonding force between silicon and carbon is insufficient, making them prone to deintercalation and deintercalation under winding and cyclic expansion pressure.
[0003] Therefore, how to provide a negative electrode that can reduce irreversible capacity loss, suppress cycling side reactions, and take into account rate performance, while also having high energy density, high initial coulombic efficiency, and long cycle life, has become an urgent problem to be solved. Summary of the Invention
[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a negative electrode sheet, a cylindrical battery, and a power supply device, which can achieve a significant improvement in initial coulombic efficiency and improved cycle stability, and can still maintain a high reversible capacity under high-rate discharge conditions.
[0005] To solve the above-mentioned technical problems, the present invention is implemented as follows: According to one aspect of the present invention, a negative electrode sheet is provided, comprising: a current collector, and an active coating on at least one surface of the current collector in the thickness direction; the active coating comprises composite microspheres, the composite microspheres comprising a porous carbon framework and silicon particles; The silicon particles are at least partially disposed in the porous carbon framework, and at least a portion of the surface of the active particles is coated with a carbon coating layer. The specific surface area of the composite microspheres is 1 m². 2 / g~5m 2 / g; and the composite microspheres also satisfy: C5 / C 0.2 ≥0.80, C 0.2 ≠0; Wherein, C5 is the reversible specific capacity of the composite microspheres at a current density of 5C, in mAh / g; C 0.2 The reversible specific capacity of the composite microspheres at a current density of 0.2C is expressed in mAh / g.
[0006] In some of these embodiments, the median particle size D of the composite microspheres v50 The size ranges from 5μm to 10μm.
[0007] In some embodiments, the compaction density of the negative electrode sheet is ρ el 1.50g / cm 3 ≤ρ el ≤1.70g / cm 3 .
[0008] In some embodiments, the areal density of the active coating on one side of the negative electrode sheet is 4.0 mg / cm³. 2 ~7.0mg / cm 2 .
[0009] In some embodiments, the silicon particles have a particle size of 1 nm to 10 nm.
[0010] In some of these embodiments, the particle size D of the silicon particles v10 ≥3μm, D v90 ≤15μm.
[0011] In some of these embodiments, the SPAN value of the silicon particles is less than or equal to 1.2.
[0012] In some of these embodiments, the thickness of the carbon coating layer is 5 nm to 20 nm.
[0013] In some embodiments, the total pore volume of the porous carbon framework is 0.70 cm³. 3 g~1.20cm 3 / g.
[0014] In some of these embodiments, the sphericity of the composite microspheres is greater than or equal to 0.85.
[0015] In some embodiments, the porosity of the active coating is 15% to 30%.
[0016] In some embodiments, the tap density of the composite microspheres is 0.60 g / cm³. 3 ~0.90g / cm 3 .
[0017] In some embodiments, the thickness expansion rate of the negative electrode sheet is Δh / h0, Δh / h0 ≤ 20%, and Δh = h1 - h0; where h0 is the initial thickness of the negative electrode sheet and h1 is the thickness of the negative electrode sheet after 600 cycles.
[0018] In some of these embodiments, the mass percentage of the silicon particles is w, based on the total mass of the composite microspheres. Si 40wt%≤w Si ≤58wt%.
[0019] In some embodiments, the active coating further includes a binder comprising at least one of styrene-butadiene rubber and polyamic acid; the binder accounts for 1 wt% to 4 wt% of the total mass of the composite microspheres.
[0020] In some embodiments, the active coating further includes a conductive agent, wherein the conductive agent accounts for 0.5 wt% to 1.5 wt% of the total mass of the composite microspheres.
[0021] In some of these embodiments, the total mass percentage of carbon is 42 wt% to 50 wt% based on the total mass of the composite microspheres.
[0022] According to another aspect of the present invention, the present invention also provides a cylindrical battery, comprising: a positive electrode, a separator, and a negative electrode, wherein the negative electrode comprises the negative electrode as described in any of the above embodiments; The cylindrical battery satisfies the following: Ev≥[C C ×(100-w Si ) / 100+C Si ×w Si / 100]×V avg ×ρ el ×f cell ; Among them, C C The specific capacity of the porous carbon framework is expressed in mAh / g; C Si The specific capacity of the silicon particles is expressed in mAh / g; V. avg f is the average discharge voltage of the cylindrical battery, in V. cell Ev is the energy conversion factor of the cylindrical battery, which is dimensionless; Ev is the volumetric energy density of the cylindrical battery, in Wh / L.
[0023] In some of these embodiments, 300mAh / g≤C C ≤380mAh / g.
[0024] In some of these embodiments, 1800mAh / g≤C Si ≤2400mAh / g.
[0025] In some of these implementations, 3.40V ≤ V avg ≤3.70V.
[0026] In some of these implementations, 0.09 ≤ f cell ≤0.13.
[0027] In some of these implementations, Ev ≥ 650 Wh / L.
[0028] In some of these implementations, when 45wt%≤w Si ≤58wt% and 1.55g / cm³ 3 ≤ρ el ≤1.70g / cm 3 When Ev satisfies: Ev≥700Wh / L.
[0029] In some embodiments, the cylindrical battery has a DC internal resistance (DCR) of less than or equal to 5 mΩ when charged to 4.2V.
[0030] In some embodiments, the positive electrode includes a positive electrode material, which includes a ternary layered oxide LiNi. x Co y Mn z O2; Where x:y:z=(0.5~0.9):(0.05~0.2):(0.05~0.3).
[0031] According to another aspect of the present invention, the present invention also provides an electrical device comprising: a cylindrical battery as described in any of the above embodiments.
[0032] Implementing the technical solution of the present invention has at least the following beneficial effects: The negative electrode in this invention achieves this by controlling the specific surface area of the composite microspheres to be between 1 and 5 m². 2 The range of / g is extremely low, and it satisfies C5 / C 0.2 With a specific surface area ≥0.80, the active lithium consumed during the initial charge-discharge process due to electrolyte decomposition on the active material surface to form an SEI film is significantly reduced, increasing the initial coulombic efficiency to over 85% without the need for additional pre-lithiation treatment. Simultaneously, the extremely low specific surface area limits the continuous contact between the electrolyte and the internal silicon during cycling, effectively suppressing side reactions and improving capacity retention over long cycles. Furthermore, the composite microspheres maintain a high reversible capacity even under 5C high-rate discharge conditions, balancing high energy density and fast-charging capability.
[0033] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0034] The technical solution of the present invention and how the technical solution of the present invention solves the above-mentioned technical problems are described in detail below with specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments. The embodiments of the present invention will be described below.
[0035] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0036] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0037] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0038] Currently, all-tab cylindrical lithium-ion batteries employ an all-tab current collector design and a tabless welding structure. The positive and negative current collectors are led out along the winding direction and welded to the current collector plate. The electron transport path changes from the point contact of the traditional single tab to surface contact, reducing battery internal resistance and improving fast charging capability. Due to the large battery size and high winding tightness, higher requirements are placed on the negative electrode material, namely, it needs to possess high specific capacity, low and reversible volume expansion rate, and long cycle life. Silicon has a high theoretical specific capacity, but it undergoes volume expansion exceeding 300% during charge and discharge, easily leading to electrode pulverization, continuous rupture and regeneration of the solid electrolyte interface film, and electrode cyclic expansion. Silicon-carbon deposition technology chemically deposits nano-silicon particles into a porous carbon framework to form micron-sized spherical composite microspheres, aiming to solve the problems of insufficient conductivity, volume expansion, and poor cycle stability of silicon. However, the related technologies still have the following shortcomings: First, the bonding force between silicon nanoparticles and carbon skeleton is insufficient, and they are prone to deintercalation under winding and cyclic expansion pressure; Second, the porous structure design fails to achieve a balance between buffering volume expansion and maintaining compaction density, affecting volumetric energy density; Third, there is a lack of systematic material design guidelines for the mechanical constraints and energy requirements of all-tab cylindrical batteries, especially a lack of quantitative description of the relationship between silicon addition and battery volumetric energy density; Fourth, the specific surface area of the related deposited silicon-carbon materials is relatively high, resulting in a low initial coulombic efficiency, which makes it difficult to meet the battery's requirement for high initial efficiency.
[0039] The researchers of this invention discovered that the drastic volume change of silicon particles during lithium insertion / extraction requires sufficient buffer space in the carbon skeleton. However, when the pore volume of the porous carbon skeleton is insufficient, the microspheres are prone to cracking, while excessive pore volume leads to a decrease in compaction density, directly reducing the volumetric energy density of the battery. Secondly, an excessively high specific surface area causes more irreversible reduction reactions of the electrolyte on the surface of the active material, consuming a large amount of active lithium when forming a solid electrolyte interface film, resulting in a decrease in initial coulombic efficiency. It also exacerbates the continuous side reactions between the electrolyte and silicon particles during cycling. Thirdly, the compaction density of the negative electrode sheet is directly related to the stiffness and processing adaptability of the electrode sheet during the winding process. Too low a compaction density will affect the strength of the electrode sheet, while too high a compaction density may crush the internal pore structure of the microspheres, losing the buffering capacity against silicon volume expansion.
[0040] In view of the technical problems existing in the prior art, the present invention proposes a negative electrode sheet, a cylindrical battery, and an electrical device, wherein the active coating comprises composite microspheres composed of a porous carbon framework and silicon particles, and at least a portion of the surface of the composite microspheres is coated with a carbon coating layer. This is achieved by controlling the specific surface area of the composite microspheres to 1 m². 2 / g to 5m 2 The system achieves a significant improvement in initial coulombic efficiency and cycle stability by controlling the silicon particle mass fraction, carbon coating thickness, porous carbon skeleton pore volume, negative electrode compaction density, single-sided active coating areal density, microsphere morphology, and electrode porosity. Furthermore, by limiting the types and amounts of binders and conductive agents, a quantitative coupling relationship between silicon addition and battery volumetric energy density is established. Under the specific mechanical constraints of a full-tab cylindrical battery, this synergistic optimization of high specific energy, high initial efficiency, and long cycle performance is achieved.
[0041] The specific technical solution of the present invention is as follows: In some embodiments of the present invention, a negative electrode sheet is provided, comprising: a current collector, and an active coating on at least one side surface of the current collector in the thickness direction; the active coating comprises composite microspheres, the composite microspheres comprising a porous carbon skeleton and silicon particles; the silicon particles are at least partially disposed in the porous carbon skeleton, and at least a portion of the surface of the active particles is coated with a carbon coating layer.
[0042] The specific surface area of the composite microspheres is 1 m². 2 / g~5m 2 / g; and the composite microspheres also satisfy: C5 / C 0.2 ≥0.80, C 0.2 ≠0; where C5 is the reversible specific capacity of the composite microspheres at a current density of 5C, in mAh / g; C 0.2The reversible specific capacity of the composite microspheres at a current density of 0.2C is expressed in mAh / g.
[0043] As an example, the current collector can be a metal foil made of a metallic material, such as copper foil or copper alloy foil. An active coating is disposed on one or both surfaces of the current collector along its thickness direction. It is understood that the active coating may be on a portion of one surface of the current collector, or it may be on the entire surface of one surface of the current collector; this invention does not specifically limit this. The active coating includes composite microspheres, which comprise a porous carbon framework. The pores of the porous carbon framework contain silicon particles with at least a carbon-coated surface. It is also understood that some of the silicon particles are disposed on the surface of the porous carbon framework.
[0044] Furthermore, the researchers of this invention discovered that when the specific surface area of the silicon-carbon composite material is high, during the first charge-discharge process, the electrolyte undergoes irreversible reduction and decomposition on the surface of the active material, forming a solid electrolyte interphase (SEI) film. This consumes a large amount of active lithium, resulting in a low initial coulombic efficiency (ICE). In addition, the high specific surface area exacerbates the continuous side reactions between the electrolyte and internal silicon particles during cycling, causing the SEI film to thicken continuously, increasing the battery's internal resistance, decreasing capacity retention, and making it difficult to maintain reversible capacity at high rates. Therefore, research has shown that if the specific surface area of the composite microspheres can be controlled within an extremely low range, the active lithium consumed in SEI film formation can be significantly reduced, while limiting the continuous contact between the electrolyte and silicon, thereby improving both the initial coulombic efficiency and cycle stability. Furthermore, by ensuring that the ratio of the reversible specific capacity of the composite microspheres at 5C to 0.2C is not less than 0.80, a high reversible capacity can be maintained even under rapid charge-discharge conditions, thus achieving a synergy between high energy density and fast charging capability.
[0045] The BET specific surface area of the composite microspheres was determined at 77 K using the nitrogen adsorption-desorption isotherm method and calculated using the BET multilayer adsorption theory. The specific surface area of the composite microspheres can reach 1 m². 2 / g, 1.5m 2 / g、2m 2 / g, 2.5m 2 / g, 2.8m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g, 4.5m 2 / g or 5m 2Any value in / g or any point between any two; thus, the initial coulombic efficiency can reach over 85%. If the specific surface area of the composite microspheres is greater than the above range, its initial coulombic efficiency is usually less than 80% because the high specific surface area exposes a large number of active sites, exacerbating electrolyte decomposition and active lithium consumption. If the specific surface area of the composite microspheres is less than the above range, although side reactions can be further reduced, it will lead to a decrease in the wettability of the electrolyte to the active material, and an increase in the transport impedance of lithium ions on the surface of the microspheres, which will affect the rate performance. The low specific surface area of the composite microspheres originates from the dense outer surface and closed-pore structure formed by the deposition process, with very few external openings, making it difficult for nitrogen molecules to enter the internal pores. This structural feature also makes it difficult for the electrolyte to penetrate into the interior of the microspheres during cycling, thereby effectively suppressing the continuous side reactions between the internal silicon particles and the electrolyte, which is beneficial to long-term cycling stability, for example, achieving a capacity retention of over 82% after 600 cycles. Furthermore, limiting C5 / C 0.2 C5 / C 0.2 The C5 / C value can be any value from 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, or higher; this allows the negative electrode to maintain a high reversible capacity at a high rate of 5C. This is related to the excellent electron conduction pathway provided by the carbon skeleton inside the microspheres and the shortening of the lithium-ion diffusion path by the thin and uniform carbon coating layer. If C5 / C... 0.2 A specific surface area below 0.80 indicates significant capacity decay at high rates, failing to meet fast charging requirements. This is typically due to either an excessively thick carbon coating leading to increased lithium-ion diffusion resistance or insufficient conductivity of the carbon framework. Therefore, the specific surface area of the composite microspheres should be controlled between 1 and 5 m². 2 / g and satisfy C5 / C 0.2 A value of ≥0.80 is used to address the issues of low initial coulombic efficiency, numerous side reactions, and difficulty in achieving rate performance in high specific surface area silicon-carbon materials.
[0046] In some embodiments, the median particle size D of the composite microspheres v50 The size ranges from 5μm to 10μm.
[0047] For example, the median particle size D of the composite microspheres v50 The particle size can be any value between 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, or 10μm, or any point value between any two; the median particle size of the composite microspheres is controlled within 5~10μm, which allows for denser particle packing, improved tap density and coating uniformity, and reduces the likelihood of localized stress concentration during rolling. If D v50 If the particle size is too small, for example, less than 5 μm, the number of contact points between particles increases, making it easy to form agglomerates, which leads to difficulties in slurry dispersion. Furthermore, the porosity after compaction is too low, which is not conducive to electrolyte penetration. If D...v50 If the particle size is too large, for example, greater than 10 μm, the interparticle voids increase, making it difficult to improve the electrode compaction density. Furthermore, larger particles generate greater absolute stress during cyclic expansion, easily leading to microsphere cracking and electrode deformation. It is understandable that the median particle size D... v50 The determination is performed using laser diffraction, for example, with a Malvern particle size analyzer, using water or ethanol as the dispersion medium.
[0048] In some embodiments, the compaction density of the negative electrode sheet is ρ el 1.50g / cm 3 ≤ρ el ≤1.70g / cm 3 .
[0049] For example, the compaction density ρ of the negative electrode sheet el It can be 1.50 g / cm³ 3 1.52g / cm 3 1.55g / cm 3 1.58g / cm 3 1.60g / cm 3 1.62g / cm 3 1.65g / cm 3 1.68g / cm 3 Or 1.70g / cm 3 The value of any one of or any point between any two of them; the compaction density is maintained at 1.50 g / cm³. 3 ~1.70g / cm 3 On the one hand, this meets the electrode stiffness requirements of the battery winding process, preventing wrinkles or breakage during winding; on the other hand, it avoids crushing the microsphere pore structure and losing buffer space. If the pressure is less than the above range, the electrode stiffness is insufficient, making it prone to deformation during winding, and the active material bulk density is low, leading to a decrease in the battery's volumetric energy density. If the pressure is greater than the above range, the rolling pressure is too high, irreversibly damaging the internal pore structure of the composite microspheres, resulting in the loss of buffer capacity for volume expansion, a sharp increase in Rct and DCR during cycling, and accelerated capacity decay. It is understandable that the compaction density ρ... el It can be calculated by measuring the electrode mass and thickness and then subtracting the current collector mass and thickness.
[0050] In some embodiments, the areal density of the single-sided active coating in the negative electrode sheet is 4.0 mg / cm³. 2 ~7.0mg / cm 2 .
[0051] For example, the areal density of the active coating on one side of the negative electrode sheet can be 4.0 mg / cm³. 2 4.5 mg / cm 25.0 mg / cm 2 5.5 mg / cm 2 6.0 mg / cm 2 6.5 mg / cm 2 Or 7.0 mg / cm 2 The areal density is any one of the values or any point between any two of them; if the areal density is too low, the active material loading per unit area of the battery is insufficient, and the energy density is limited; if the areal density is too high, the electrode thickness increases, the diffusion path of lithium ions in the thick coating increases, the concentration polarization increases, the rate performance decreases, and the stress accumulation caused by cycle expansion is more significant, which is not conducive to long cycle.
[0052] In some embodiments, the silicon particles have a particle size of 1 nm to 10 nm.
[0053] For example, the silicon particle size can be any value between 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, or 10nm. If it is smaller than the above range, the absolute volume expansion of a single silicon particle is significantly reduced, which can reduce local stress. If the particle size is larger than 10nm, the absolute expansion increases, which can easily lead to mechanical damage to the internal structure of the microspheres. It is understood that the silicon particle size is statistically analyzed using transmission electron microscopy to determine the particle size of at least 100 silicon particles and to calculate D. v10 D v50 and D v90 .
[0054] In some embodiments, the particle size D of the silicon particles v10 ≥3μm, D v90 ≤15μm. Optional, the particle size D of the silicon particles. v10 It can be any value of 3μm, 4μm, 5μm and above, D v90 It can be any value of 15μm, 14μm, 13μm and below.
[0055] In some embodiments, the SPAN value of the silicon particles is less than or equal to 1.2.
[0056] For example, the particle size distribution span SPAN = (D v90 -D v10 ) / D v50 A particle size distribution span (SPAN) of less than or equal to 1.2 ensures particle size uniformity and avoids localized stress concentration caused by larger particles, thus preventing microsphere cracking. The span can be 1.20, 1.15, 1.10, 1.05, 1.00, or lower. If the particle size distribution span is too large, large particles in the wide distribution will become stress concentration points and preferred failure sites.
[0057] In some embodiments, the thickness of the carbon coating layer is 5 nm to 20 nm.
[0058] For example, the thickness t of the carbon coating layer can be any value or any point between 5nm, 8nm, 10nm, 12nm, 15nm, 18nm, or 20nm. In this way, the carbon coating layer can effectively isolate the silicon from direct contact with the electrolyte during cycling, preventing the electrolyte from continuously decomposing on the silicon surface to form an unstable SEI film. Simultaneously, it does not significantly increase the lithium-ion diffusion resistance due to excessive carbon layer thickness, thus achieving a balance between cycle stability and rate performance. If the carbon layer thickness is less than 5nm, the carbon layer is insufficient to completely cover the silicon particle surface, resulting in an unstable SEI film during cycling and accelerated capacity decay. If the carbon layer thickness is greater than 20nm, the diffusion path of lithium ions through the carbon layer becomes longer, leading to increased charge transfer resistance, decreased capacity retention at 5C rate, and a significant increase in battery DCR. It is understood that the thickness t of the carbon coating layer is directly observed using a high-resolution transmission electron microscope.
[0059] In some embodiments, the total pore volume of the porous carbon framework is 0.70 cm³. 3 g~1.20cm 3 / g.
[0060] For example, the total pore volume V of the porous carbon framework pore It can be 0.70cm 3 g, 0.75cm 3 g, 0.80cm 3 g, 0.85cm 3 g, 0.90cm 3 g, 0.95cm 3 g, 1.00cm 3 g, 1.05cm 3 g, 1.10cm 3 g, 1.15cm 3 g or 1.20cm 3 Any value of g, or any point between any two; thus, sufficient buffer space is provided to accommodate the volume expansion of silicon, preventing microsphere cracking and rapid capacity decay due to insufficient pore volume; the upper limit of pore volume is determined by the compressibility constraint of the electrode. If it exceeds the above range, the microsphere structure is loose, and the compaction density is difficult to reach 1.50 g / cm³. 3This reduces the volumetric energy density of the battery. The lower limit of the pore volume is determined by the buffering requirement of silicon volume expansion. Silicon expands by more than 300% during lithium intercalation, requiring sufficient pore volume to absorb this expansion. If the pore volume is less than the above range, the expansion stress cannot be fully released, the microspheres rupture, and the cycle capacity decreases sharply. In addition, the silicon particles are uniformly distributed inside the porous carbon framework. When observing the cross-section with a scanning electron microscope, the silicon particle exposure ratio on the surface of a single microsphere is no more than 5%. This allows most of the silicon particles to be deeply buried in the carbon framework and covered by the carbon coating layer, with very little silicon directly exposed to the electrolyte, further suppressing side reactions. Through the synergistic effect of the above structure, the negative electrode can achieve a capacity retention rate of over 83% after 600 cycles, and has excellent rate performance. It can be understood that the total pore volume V of the porous carbon framework is... pore The determination was performed using nitrogen adsorption-desorption method, and the calculation was performed using BJH or DFT models.
[0061] In some embodiments, the sphericity of the composite microspheres is greater than or equal to 0.85.
[0062] For example, sphericity can be any value of 0.85, 0.88, 0.90, 0.92, 0.95, or higher. High sphericity contributes to the close packing and uniform coating of particles, and reduces the likelihood of localized stress concentration points during rolling, thereby improving the consistency and processability of the electrode. Understandably, sphericity is calculated by analyzing scanning electron microscopy images and statistically analyzing the projected area and perimeter of at least 100 microspheres to determine the average sphericity.
[0063] In some embodiments, the porosity of the active coating is 15% to 30%.
[0064] For example, the porosity of an active coating refers to the percentage of the total volume of the coating, excluding the solid active material, conductive agent, and binder. The porosity can be any value from 15%, 18%, 20%, 22%, 25%, 28%, or 30%, or any value between any two. This provides sufficient liquid-phase transport channels for lithium ions, which helps reduce concentration polarization and improve rate performance. Simultaneously, it can accommodate the volume expansion of silicon to a certain extent, reducing the overall thickness expansion of the electrode. If the porosity is too low, ion transport is hindered, and the DC internal resistance increases; if the porosity is too high, the coating structure is loose, electron conductivity deteriorates, and the compaction density decreases, affecting the volumetric energy density. It is understood that porosity can be determined by mercury intrusion porosimetry or image analysis.
[0065] In some embodiments, the tap density of the composite microspheres is 0.60 g / cm³. 3 ~0.90g / cm 3 .
[0066] For example, the tap density of the composite microspheres can be 0.60 g / cm³.3 0.65g / cm 3 0.70g / cm 3 0.75g / cm 3 0.80g / cm 3 0.85g / cm 3 or 0.90g / cm 3 The tap density is any value between any one of the two or any two of the values; the tap density reflects the flowability and filling properties of the powder, and a higher tap density is beneficial for obtaining electrodes with high areal density and high compaction density. It can be understood that the tap density of composite microspheres can be determined by a tap density meter after a certain number of tapping cycles.
[0067] In some embodiments, the thickness expansion rate of the negative electrode sheet is Δh / h0, Δh / h0≤20%, and Δh=h1-h0; where h0 is the initial thickness of the negative electrode sheet and h1 is the thickness of the negative electrode sheet after 600 cycles.
[0068] For example, the thickness expansion rate of the negative electrode sheet can be any value of 20%, 18%, 15%, 12%, 10%, or less. Controlling it below 20% allows the pore structure inside the composite microspheres and the carbon coating layer to effectively buffer the volume change of silicon, preventing irreversible deformation of the electrode sheet and shedding of active materials, thus ensuring a long cycle life. If the expansion rate exceeds 20%, the electrode structure is severely damaged, the electrical contact between active materials and between the active materials and the current collector deteriorates, capacity decays faster, and safety issues may arise due to the electrode sheet expanding and encroaching on the internal space of the battery. It can be understood that the thickness expansion rate of the negative electrode sheet after 600 cycles is calculated by measuring the thickness change of the electrode sheet after formation and after 600 cycles, and calculating the ratio of the thickness increase to the original thickness.
[0069] In some embodiments, based on composite microspheres, the mass fraction of silicon particles is 40wt% to 58wt%.
[0070] For example, based on composite microspheres, the mass fraction w of silicon particles SiThe silicon content can be any value between 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, 50wt%, 52wt%, 53.3wt%, 54wt%, 56wt%, or 58wt%, or any point between any two. When the silicon content is within the above range, the reversible specific capacity of the composite microspheres can be adjusted between approximately 940mAh / g and 1380mAh / g, while maintaining good cycle stability. If it is less than the above range, although the cycle stability is excellent, the specific capacity of the active material is insufficient, making it difficult for the battery volumetric energy density to exceed 650Wh / L. If it is greater than the above range, although the initial reversible capacity is high, the volume expansion of silicon during cycling exceeds the buffering capacity of the carbon skeleton, leading to microsphere cracking, failure of electrical contacts of the active material, and a sharp drop in capacity retention to 68.5% after 600 cycles, and severe degradation of the battery volumetric energy density in the later stages of cycling. It is understandable that the silicon particle mass fraction w Si It can be determined by heating to 800°C in air atmosphere using thermogravimetric analysis.
[0071] In some embodiments, the active coating further includes a binder, which includes, but is not limited to, one or more of styrene-butadiene rubber and polyamic acid; the mass percentage of the binder is 1 wt% to 4 wt% based on the total mass of the composite microspheres.
[0072] For example, the specific amount of adhesive can be any one of 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, or 4wt%, or any point value between any two; styrene-butadiene rubber has high elasticity and good adhesion, which can maintain the adhesion between the coating and the current collector when the volume of silicon particles changes repeatedly, preventing the active material from falling off. Polyamic acid can be imidized at high temperature to form polyimide, which has higher mechanical strength and thermal stability.
[0073] In some embodiments, the active coating also includes a conductive agent, the mass percentage of which is 0.5wt% to 1.5wt% based on the total mass of the composite microspheres.
[0074] For example, the conductive agent can be conductive carbon black, carbon nanotubes or graphene, etc., and the mass percentage can be any one of 0.5wt%, 0.8wt%, 1wt%, 1.2wt% or 1.5wt% or any point value between any two; a lower amount of conductive agent can meet the electron transport requirements without significantly reducing the proportion of active material, which is beneficial to improving energy density.
[0075] In some embodiments, the total mass percentage of carbon elements is 42wt% to 50wt% based on the total mass of the composite microspheres.
[0076] For example, the total mass percentage of carbon can be any one of 42wt%, 44wt%, 46wt%, 48wt%, or 50wt%, or any value between any two; this ensures the material's low specific surface area and structural integrity during cycling. If it is less than the above range, the carbon framework is insufficient to buffer the volume expansion of silicon, the coating layer may be incomplete, leading to accelerated cycle decay; if it is greater than the above range, the silicon content of the active material is relatively reduced, the specific capacity decreases, and the high capacity advantage of silicon cannot be fully utilized. It can be understood that the total mass percentage of carbon is the percentage of the total mass of the porous carbon framework carbon and the carbon coating layer carbon in the composite microspheres to the total mass of the composite microspheres.
[0077] Optionally, the mass ratio m of carbon to silicon nanoparticles in the carbon coating layer C :m Si It can also satisfy 0.30~0.60, such as any one or any two of 0.30, 0.35, 0.40, 0.45, 0.50, 0.55 or 0.60, thus taking into account both the integrity of the silicon surface coating and the control of lithium ion diffusion resistance.
[0078] Optionally, the carbon coating layer can be formed by pre-oxidation and carbonization of polyvinylpyrrolidone (PVP). Specifically, PPVP is pre-oxidized in air at 150°C for 10 hours, followed by carbonization at 350°C for 1 hour in an inert atmosphere, to form a uniform amorphous carbon layer on the surface of silicon particles and porous carbon framework. By controlling the amount of PPVP and the heat treatment parameters, the carbon layer thickness can be adjusted to the range of 5 nm to 20 nm.
[0079] In some embodiments of the present invention, a cylindrical battery is also provided, comprising: a positive electrode, a separator, and a negative electrode, wherein the negative electrode comprises the negative electrode of any of the above embodiments; wherein the cylindrical battery satisfies: Ev≥[C C ×(100-w Si ) / 100+C Si ×w Si / 100]×V avg ×ρ el ×f cell ; Among them, C C C represents the specific capacity of the porous carbon framework, in mAh / g. Si Specific capacity of silicon particles, unit: mAh / g; V avg The average discharge voltage of a cylindrical battery, in V; f cell Ev is the energy conversion factor of the cylindrical battery, which is dimensionless; Ev is the volumetric energy density of the cylindrical battery, in Wh / L.
[0080] For example, the energy conversion factor (fcell) refers to the dimensionless coefficient that converts the energy density at the electrode level to the energy density at the battery level. It comprehensively reflects the influence of the volume ratio and N / P ratio of non-active components such as the positive electrode, negative electrode, separator, electrolyte, current collector, and casing in the battery. The positive electrode sheet includes the positive electrode current collector, which can be aluminum foil or aluminum alloy foil, etc. The positive electrode sheet includes the positive electrode active material, which can be ternary material, electrolyte material, etc. The present invention does not specifically limit the separator and electrolyte. The cylindrical battery satisfies the above relationship, and the high specific energy, high first-efficiency, and long cycle performance are synergistically optimized under the specific mechanical constraints of the all-tab cylindrical battery.
[0081] In some embodiments, 300mAh / g≤C C ≤380mAh / g. For example, the specific capacity C of the porous carbon framework... C It can be any point value between any one or any two of 300mAh / g, 310mAh / g, 320mAh / g, 330mAh / g, 340mAh / g, 350mAh / g, 360mAh / g, 370mAh / g, 375mAh / g, or 380mAh / g.
[0082] In some embodiments, 1800mAh / g≤C Si ≤2400mAh / g. For example, the specific capacity C of silicon particles... Si It can be any point value between any one of 1800mAh / g, 1900mAh / g, 2000mAh / g, 2100mAh / g, 2200mAh / g, 2300mAh / g, 2350mAh / g, 2380mAh / g, 2390mAh / g or 2400mAh / g.
[0083] In some embodiments, 3.40V ≤ V avg ≤3.70V. For example, the average discharge voltage V of a cylindrical battery... avg It can be any point value between any one of 3.40V, 3.43V, 3.46V, 3.49V, 3.52V, 3.55V, 3.58V, 3.61V, 3.64V, 3.67V or 3.70V.
[0084] In some embodiments, 0.09 ≤ f cell ≤0.13. For example, the energy conversion factor f of a cylindrical battery... cell It can be any one of 0.09, 0.10, 0.11, 0.12 or 0.13, or any point value between any two.
[0085] In some embodiments, Ev ≥ 650 Wh / L. Exemplarily, the volumetric energy density Ev of a cylindrical battery can be any value of 650 Wh / L, 660 Wh / L, 680 Wh / L, or higher.
[0086] In some embodiments, when 45wt%≤w Si ≤58wt% and 1.55g / cm³ 3 ≤ρ el ≤1.70g / cm 3 When Ev satisfies: Ev ≥ 700Wh / L. For example, in a cylindrical battery including the negative electrode sheet in any of the above embodiments, when the silicon content in the negative electrode sheet is within the above range and the compaction density of the negative electrode sheet is within the above range, the volumetric energy density Ev of the cylindrical battery can be any value of 700Wh / L, 720Wh / L, 750Wh / L, or higher.
[0087] In some embodiments, the DC internal resistance (DCR) of the cylindrical battery when charged to 4.2V is less than or equal to 5mΩ.
[0088] In some embodiments, the positive electrode includes a positive electrode material, which includes, but is not limited to, ternary layered oxide LiNi. x Co y Mn z O2; where x:y:z=(0.5~0.9):(0.05~0.2):(0.05~0.3).
[0089] Optionally, the positive electrode can be made of high-capacity positive electrode materials such as lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium iron phosphate, and the separator can be a polyolefin porous membrane or a composite membrane coated with a ceramic layer. The positive electrode, separator, and negative electrode are assembled into an electrode assembly by winding or stacking, housed in a battery casing, and electrolyte is injected. After formation and capacity testing, the final battery is obtained. This battery is particularly suitable for all-tab cylindrical batteries because its negative electrode has low specific surface area, high initial efficiency, high volumetric energy density, and long cycle life. Combined with the inherent low internal resistance of the all-tab structure, it can achieve higher power output and a longer service life.
[0090] In some embodiments of the present invention, an electrical device is also provided, comprising: the cylindrical battery in any of the above embodiments.
[0091] Optionally, the electrical devices can be vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, power tools, energy storage devices, amusement equipment, elevators and lifting equipment, etc. Electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, or electric airplane toys, etc.; power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc.; energy storage devices can be energy storage walls, base station energy storage, container energy storage, etc.; amusement equipment can be carousels, drop towers, etc. The aforementioned vehicles can be fuel-powered vehicles, natural gas vehicles, or new energy vehicles. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A battery is installed inside the vehicle, which can be located at the bottom, front, or rear of the vehicle. The battery can be used to power the vehicle; for example, the battery can serve as the vehicle's operating power source. The vehicle may also include a controller and a motor. The controller controls the battery's power supply to the motor, for example, to meet the vehicle's power needs during starting, navigation, and driving. The battery can serve not only as the vehicle's operating power source but also as its driving power source, replacing or partially replacing fuel or natural gas to provide propulsion.
[0092] The diaphragm used in this embodiment is a diaphragm used in the art and is not particularly limited herein. All solvents and substances in this invention are commercially available.
[0093] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.
[0094] The present invention will be specifically described below with reference to the embodiments, but the implementation and protection of the present invention are not limited thereto. The following embodiments are only some embodiments of the present invention and are not intended to limit the present invention.
[0095] Example 1 The polystyrene (PS):PVP:Si:CB (carbon black):CNT (carbon nanotubes) were dissolved in DMF (N,N-dimethylformamide) at a mass ratio of PS (polystyrene):PVP:Si:CB (carbon black):CNT (carbon nanotubes) = 6:6:5:2:1. The mixture was stirred at 80°C for 3 hours, then Si nanoparticles (D50 = 5 nm), carbon nanotubes, and Ketjenblack EC-600JD were added, and the mixture was ultrasonically dispersed for 2 hours. Electrostatic spraying was performed at 19 kV, with a nozzle-to-collecting plate distance of 18 cm and a feed rate of 1.5 mL / h. Pre-oxidation was carried out at 150°C for 10 hours, followed by heating at 350°C for 1 hour. Inert atmosphere carbonization was performed at 700°C for 3 hours using Ar gas, with a heating rate of 10°C / min.
[0096] Electrode preparation: A slurry was prepared using styrene-butadiene rubber (SBR) as a binder (2wt%), conductive carbon black as a conductive agent (1wt%), and PeSiC active material (97wt%). This slurry was coated onto copper foil (9μm thick). An 8mm blank area was left along the winding direction for the negative electrode current collector to form the negative electrode tab. The electrode was then rolled to a compaction density of 1.60 g / cm³. 3 Assemble a 4680 all-tab cylindrical battery, with the positive and negative all-tabs connected to their respective current collectors via laser welding.
[0097] Preparation of the positive electrode sheet: The positive electrode uses lithium nickel cobalt manganese oxide NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2, D v50 =7.8μm) was used as the positive electrode active material. 96wt% NCM811, 2wt% conductive carbon black SuperP, and 2wt% polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) and stirred until homogeneous to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry was uniformly coated on both sides of a 12μm aluminum foil, dried in a three-stage gradient at 60℃, 90℃, and 120℃, and then rolled to a compaction density of 3.50 g / cm³. 3 After slitting, the positive electrode sheet is obtained. An 8mm blank area is left along the winding direction to form the positive electrode tab, with a single-sided areal density of 18mg / cm³. 2 .
[0098] The diaphragm is made of polyethylene (PE) base membrane with a total thickness of 12μm and a 2μm Al2O3 ceramic coating on one side.
[0099] Electrolyte: In a drying chamber with a dew point < -40℃, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6, battery grade) is added to a molar concentration of 1.2 mol / L, followed by the addition of 8 wt% fluoroethylene carbonate (FEC) and 1.5 wt% vinylene carbonate (VC). The mixture is stirred until completely dissolved to obtain the electrolyte.
[0100] Key parameter: w Si =53.3wt%, t=10nm, V pore =1.02cm 3 / g, SBET=2.8m 2 / g, ρ el =1.60g / cm 3 D v50 =7.5μm.
[0101] Electrochemical performance: C 0.2 (0.2C, week 600) = 1280mAh / g, CR600 = 86.2%, C5 / C 0.2 =0.85, Rct=38Ω, Ev=738Wh / L, DCR=3.8mΩ, ICE=89.5%, total tab welding internal resistance Rtab=0.28mΩ.
[0102] Example 2 The difference between Example 2 and Example 1 is that the PS / PVP / Si feeding ratio was adjusted to reduce the Si mass fraction in the PeSiC microspheres to 40wt%, while all other aspects are the same as in Example 1.
[0103] Electrochemical performance: C 0.2 (0.2C, week 600) = 940mAh / g, CR600 = 90.5%, C5 / C 0.2 =0.88, Rct=42Ω, Ev=604Wh / L, DCR=4.2mΩ, ICE=91.2%.
[0104] Example 3 The difference between Example 3 and Example 1 is that w Si =47wt%, all other values are the same as in Example 1.
[0105] Electrochemical performance: C 0.2 =1080mAh / g, CR600=88.3%, C5 / C 0.2 =0.86, Rct=40Ω, Ev=650Wh / L, DCR=4.0mΩ, ICE=90.5%.
[0106] Example 4 The difference between Example 4 and Example 1 is that w Si =58wt%, all other values are the same as in Example 1.
[0107] Electrochemical performance: C 0.2 =1380mAh / g, CR 600 =83.5%, C5 / C 0.2 =0.82, Rct=48Ω, Ev=785Wh / L, DCR=4.5mΩ, ICE=87.8%.
[0108] Example 5 The difference between Example 5 and Example 1 is that the PVP pre-oxidation time is shortened (150℃×5h+350℃×0.5h), reducing the thickness of the amorphous carbon coating layer to 5nm. All other aspects are the same as in Example 1.
[0109] Electrochemical performance: C 0.2 =1240mAh / g, CR600=83.8%, C5 / C 0.2 =0.78, Rct=55Ω, Ev=725Wh / L, DCR=5.2mΩ, ICE=86.5%.
[0110] Example 6 The difference between Example 6 and Example 1 is that t = 8 nm; all other aspects are the same as in Example 1. Electrochemical performance: C 0.2 =1265mAh / g, CR600=85.5%, C5 / C 0.2 =0.83, Rct=42Ω, Ev=732Wh / L, DCR=4.0mΩ.
[0111] Example 7 The difference between Example 7 and Example 1 is that t=15nm (extending the pre-oxidation time), while everything else is the same as Example 1.
[0112] Electrochemical performance: C 0.2 =1250mAh / g, CR600=87.8%, C5 / C 0.2 =0.87, Rct=35Ω, Ev=730Wh / L, DCR=3.6mΩ.
[0113] Example 8 The difference between Example 8 and Example 1 is that t=20nm (further extending the pre-oxidation time), while everything else is the same as Example 1.
[0114] Electrochemical performance: C 0.2 =1170mAh / g, CR600=87.2%, C5 / C 0.2 =0.80, Rct=33Ω, Ev=710Wh / L, DCR=4.2mΩ.
[0115] Example 9 The difference between Example 9 and Example 1 is that the PS / PVP ratio was adjusted to reduce carbon loss, thereby reducing the total pore volume to 0.70 cm³. 3 / g, ρ el It can be increased to 1.65g / cm³. 3 Everything else is the same as in Example 1.
[0116] Electrochemical performance: C 0.2 =1190mAh / g, CR600=82.5%, C5 / C 0.2 =0.82, Rct=48Ω, Ev=750Wh / L, DCR=4.5mΩ.
[0117] Example 10 The difference between this embodiment and Embodiment 1 is that V pore =0.85cm 3 / g, everything else is the same as in Example 1.
[0118] Electrochemical performance: C 0.2 =1240mAh / g, CR600=84.8%, C5 / C 0.2 =0.84, Rct=42Ω, Ev=742Wh / L, DCR=4.0mΩ.
[0119] Example 11 The difference between Example 11 and Example 1 is that V pore =1.10cm 3 / g, everything else is the same as in Example 1.
[0120] Electrochemical performance: C 0.2 =1300mAh / g, CR600=87.0%, C5 / C 0.2 =0.86, Rct=36Ω, Ev=720Wh / L, DCR=3.6mΩ, ρ el =1.55g / cm³.
[0121] Example 12 The difference between Example 12 and Example 1 is that V pore =1.20cm 3 / g, everything else is the same as in Example 1.
[0122] Electrochemical performance: C 0.2 =1310mAh / g, CR600=86.5%, C5 / C 0.2 =0.85, Rct=37Ω, Ev=702Wh / L, DCR=3.8mΩ, ρ el =1.52g / cm³.
[0123] Example 13 The difference between Example 13 and Example 1 is that the roller pressure is reduced, ρ el =1.50g / cm 3 Everything else is the same as in Example 1.
[0124] Electrochemical performance: C 0.2 =1290mAh / g, CR600=87.5%, C5 / C 0.2 =0.86, Rct=37Ω, Ev=695Wh / L, DCR=3.8mΩ.
[0125] Example 14 The difference between Example 14 and Example 1 is that ρ el =1.55g / cm 3 Everything else is the same as in Example 1.
[0126] Electrochemical performance: C 0.2 =1285mAh / g, CR600=86.8%, C5 / C 0.2 =0.85, Ev=718Wh / L, DCR=3.8mΩ.
[0127] Example 15 The difference between Example 15 and Example 1 is that ρ el =1.65g / cm 3 (The roller pressure is increased), and everything else is the same as in Example 1.
[0128] Electrochemical performance: C 0.2 =1260mAh / g, CR600=84.5%, C5 / C 0.2 =0.83, Rct=45Ω, Ev=760Wh / L, DCR=4.2mΩ.
[0129] Example 16 The difference between Example 16 and Example 1 is that ρ el =1.70g / cm 3 (Roller press to the highest set value), everything else is the same as in Example 1.
[0130] Electrochemical performance: C 0.2 =1220mAh / g, CR600=82.2%, C5 / C 0.2 =0.80, Rct=55Ω, Ev=775Wh / L, DCR=5.5mΩ.
[0131] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the amount of Si fed is reduced, making w Si =30wt%, all other values are the same as in Example 1.
[0132] Electrochemical performance: C 0.2 =680mAh / g, CR600=92.8%, C5 / C 0.2 =0.90, Rct=40Ω, Ev=510Wh / L, DCR=4.0mΩ, ICE=92.5%.
[0133] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that wt% Si = 65wt%, while all other aspects are the same as in Example 1. Electrochemical performance: C 0.2=1480mAh / g, CR600=68.5%, C5 / C 0.2 =0.72, Rct=85Ω, Ev=620Wh / L, DCR=6.5mΩ.
[0134] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the pre-oxidation step was skipped and direct carbonization (i.e., NeSiC) was performed, so that t < 3 nm. Everything else was the same as Example 1.
[0135] Electrochemical performance: C 0.2 =1160mAh / g, CR600=72.0%, C5 / C 0.2 =0.68, Rct=82Ω, Ev=590Wh / L, DCR=8.5mΩ.
[0136] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the pre-oxidation time was significantly extended (150℃×20h+350℃×3h) to make t=30nm, while all other aspects were the same as in Example 1.
[0137] Electrochemical performance: C 0.2 =1020mAh / g, CR600=85.5%, C5 / C 0.2 =0.55, Rct=32Ω, Ev=660Wh / L, DCR=8.2mΩ.
[0138] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the pore volume is reduced by increasing the CB filling ratio, V pore =0.50cm 3 / g, everything else is the same as in Example 1.
[0139] Electrochemical performance: C 0.2 =1100mAh / g, CR600=74.8%, C5 / C 0.2 =0.80, Rct=52Ω, Ev=620Wh / L, DCR=5.0mΩ.
[0140] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the amount of CB added is reduced, V pore =1.50cm 3 / g, everything else is the same as in Example 1.
[0141] Electrochemical performance: C 0.2 =1320mAh / g, CR600=85.0%, C5 / C 0.2 =0.85, ρ el Only 1.38g / cm3 Ev=565Wh / L, DCR=4.0mΩ.
[0142] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that the roller pressure is reduced, ρ el =1.40g / cm³, and everything else is the same as in Example 1.
[0143] Electrochemical performance: C 0.2 =1290mAh / g, CR600=88.5%, C5 / C 0.2 =0.86, Rct=37Ω, Ev=548Wh / L, DCR=3.8mΩ.
[0144] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that the rolling pressure is significantly increased, ρ el =1.85g / cm 3 Everything else is the same as in Example 1.
[0145] Electrochemical performance: C 0.2 =1060mAh / g, CR600=75.0%, C5 / C 0.2 =0.72, Rct=95Ω, Ev=640Wh / L, DCR=8.5mΩ.
[0146] Performance testing: 1. TGA determination of silicon content: The composite microsphere material is heated from room temperature to 800℃ in air at a rate of 10℃ / min. The residual mass at 800℃ is the silicon content (w). Si ).
[0147] 2. HRTEM detection of carbon layer thickness: The carbon layer thickness of at least 30 Si particles was statistically analyzed under field emission transmission electron microscopy (accelerating voltage 200kV), and the average value was taken.
[0148] 3. Pore volume determination: Calculated using the mercury intrusion porosimetry (MIP) method or by combining true density (He specific gravity bottle method) and tap density: V pore =1 / ρ tap -1 / ρ true Due to the extremely low specific surface area of the composite microspheres, the N2 adsorption-desorption method is limited in its application to the detection of closed pores.
[0149] 4. BET specific surface area test: Using a Micromeritics ASAP2020 or equivalent instrument, the N2 adsorption-desorption isotherm was tested at 77K, and the specific surface area was calculated using the BET method.
[0150] 5. Compacted density test: Weigh the electrode sheet using a 0.01 g balance, measure the electrode sheet thickness using a micrometer, and calculate the compacted density of the active layer after deducting the mass and thickness of the current collector.
[0151] 6. Volumetric energy density test: Charge the 4680 battery to 4.2V at a constant current and constant voltage of 0.2C, and then discharge it to 2.5V at 0.2C. Record the discharge energy E (Wh), measure the external dimensions of the battery and calculate the volume V (L). Ev = E / V.
[0152] 7. Full tab welding internal resistance test: The contact internal resistance Rtab of the full tab welding area is measured by the four-probe method, or indirectly determined by the battery DC internal resistance (DCR) test.
[0153] The test results are shown in Table 1.
[0154] Table 1 Continued from Table 1 Note: C 0.2 The reversible specific capacity at 0.2C at week 600; CR600 is the capacity retention rate at week 600; C5 / C 0.2 Rct is the 5C / 0.2C rate capacity ratio; Ev is the EIS charge transfer resistance after 2 cycles at 0.2C; Ev is the volumetric energy density of the 4680 battery (arrows indicate values after cycle decay); DCR is the DC internal resistance of the battery (4.2V charging state); ICE is the initial coulombic efficiency (half-cell 0.2C, 0.01~1.5V).
[0155] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0156] In the above embodiments, the descriptions of each embodiment have their own emphasis. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions of other embodiments. The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification.
[0157] Other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of the invention are indicated by the following claims.
[0158] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0159] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0160] It should be understood that the present invention is not limited to the precise structures described above and shown herein, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A negative electrode sheet, characterized in that, include: A current collector, and an active coating on at least one surface of the current collector in the thickness direction; The active coating includes composite microspheres, which comprise a porous carbon framework and silicon particles. The silicon particles are at least partially disposed in the porous carbon framework, and at least a portion of the surface of the active particles is coated with a carbon coating layer. The specific surface area of the composite microspheres is 1 m². 2 / g~5m 2 / g; and the composite microspheres also satisfy: C5 / C 0.2 ≥0.80, C 0.2 ≠0; Wherein, C5 is the reversible specific capacity of the composite microspheres at a current density of 5C, in mAh / g; C 0.2 The reversible specific capacity of the composite microspheres at a current density of 0.2C is expressed in mAh / g.
2. The negative electrode sheet according to claim 1, characterized in that, It also satisfies at least one of features (1) to (3): (1) The median particle size D of the composite microspheres v50 The thickness is 5μm to 10μm; (2) The compaction density of the negative electrode sheet is ρ el 1.50g / cm 3 ≤ρ el ≤1.70g / cm 3 ; (3) In the negative electrode sheet, the areal density of the active coating on one side is 4.0 mg / cm³. 2 ~7.0mg / cm 2 .
3. The negative electrode sheet according to claim 1, characterized in that, The silicon particles have a particle size of 1 nm to 10 nm; And / or, the particle size D of the silicon particles v10 ≥3μm, D v90 ≤15μm; And / or, the SPAN value of the silicon particles is less than or equal to 1.2; And / or, the thickness of the carbon coating layer is 5nm~20nm; And / or, the total pore volume of the porous carbon framework is 0.70 cm³. 3 g~1.20cm 3 / g.
4. The negative electrode sheet according to claim 1, characterized in that, The sphericity of the composite microspheres is greater than or equal to 0.85; And / or, the porosity of the active coating is 15%~30%; And / or, the tap density of the composite microspheres is 0.60 g / cm³. 3 ~0.90g / cm 3 ; And / or, the thickness expansion rate of the negative electrode sheet is Δh / h0, Δh / h0≤20%, Δh=h1-h0; where h0 is the initial thickness of the negative electrode sheet, and h1 is the thickness of the negative electrode sheet after 600 cycles.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that, Based on the total mass of the composite microspheres, the mass percentage of the silicon particles is w. Si 40wt%≤w Si ≤58wt% And / or, the active coating further includes a binder, the binder comprising at least one of styrene-butadiene rubber and polyamic acid; the binder accounts for 1wt% to 4wt% of the total mass of the composite microspheres; And / or, the active coating further includes a conductive agent, wherein the conductive agent accounts for 0.5 wt% to 1.5 wt% of the total mass of the composite microspheres; And / or, based on the total mass of the composite microspheres, the total mass percentage of carbon is 42wt%~50wt%.
6. A cylindrical battery, characterized in that, include: A positive electrode, a separator, and a negative electrode, wherein the negative electrode comprises the negative electrode as described in any one of claims 1 to 5; The cylindrical battery satisfies the following: Ev≥[C C ×(100-w Si ) / 100+C Si ×w Si / 100]×V avg ×ρ el ×f cell ; Among them, C C The specific capacity of the porous carbon framework is expressed in mAh / g; C Si The specific capacity of the silicon particles is expressed in mAh / g; V. avg f is the average discharge voltage of the cylindrical battery, in V. cell Ev is the energy conversion factor of the cylindrical battery, which is dimensionless; Ev is the volumetric energy density of the cylindrical battery, in Wh / L.
7. The cylindrical battery according to claim 6, characterized in that, Satisfying at least one of features (1) to (5): (1)300mAh / g≤C C ≤380mAh / g; (2)1800mAh / g≤C Si ≤2400mAh / g; (3)3.40V≤V avg ≤3.70V; (4)0.09≤f cell ≤0.13; (5) Ev≥650Wh / L.
8. The cylindrical battery according to claim 6, characterized in that, When 45wt%≤w Si ≤58wt% and 1.55g / cm³ 3 ≤ρ el ≤1.70g / cm 3 At that time, Ev satisfies: Ev≥700Wh / L; And / or, the DC internal resistance DCR of the cylindrical battery when charged to 4.2V is less than or equal to 5mΩ.
9. The cylindrical battery according to claim 6, characterized in that, The positive electrode includes a positive electrode material, which includes a ternary layered oxide LiNi. x Co y Mn z O2; Where x:y:z=(0.5~0.9):(0.05~0.2):(0.05~0.3).
10. An electrical device, characterized in that, include: The cylindrical battery according to any one of claims 6 to 9.
